Studi kelayakan lokasi tempat pemrosesan akhir (TPA) sampah di Kabupaten Manokwari Selatan - Ika Indrieaswati; Ishak S. Erari; Anton S. Sinery (Cassowary, 2022)
The aim of the research was to determine the feasibility level of the landfill site in south Manokwari Regency according to national standart of Indonesia no. 03-3241-1994. The method used in this study was descriptive with field observation techniques. Primary data were obtained through direct field surveys, while secondary data were obtained from government agencies or literarature studies. The data were analyzed using the buffering and overlay scoring methods with the assistance of a geographic information systems (GIS). In the regional feasibility analysis, parameters considered the feasibility of a landfill location according to national standart of Indonesia no. 03-3241-1994: rock type, groundwater level, slope, distance to river, distance to coastline, distance to airport, 25-year flood period, and protected area/nature reserves. The result of research of the 10 parameters with the measurement (scoring) that has been carried out, the prospective landfill site in the South Manokwari Regency in the first interval class, with a score of 122. This value shows that the waste landfill location is included in the interval class 32- 128 and is not feasible category.